Gender norms and the quantity-quality tradeoff: Evidence from free primary education in Africa - Matthew Collins; Eleonora Guarnieri; Helmut Rainer (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
This paper investigates the causal impact of free primary education (FPE) on fertility decisions among parents in sub-Saharan Africa, focusing on the interplay between the policy, intra-household bargaining, and cultural norms. Using Demographic and Health Survey data and exploiting the staggered rollout of FPE across 17 countries, we find that FPE reduces fertility by 0.1 children per woman and improves child survival and school enrollment. Linking these data with ethnic-level cultural norms of male dominance, we find that these effects are concentrated among ethnic groups with low male dominance, while high male-dominance groups experience minimal or opposing effects. We further show that FPE strengthens women's bargaining power in low male-dominance settings, as evidenced by increased contraceptive use, greater influence over reproductive decisions, and higher participation in household decision-making. These changes are accompanied by higher labor force participation, increased media engagement, a higher probability of divorce, and reduced tolerance for intimate partner violence. Such shifts are largely absent in high-male dominance cultures. These findings are consistent with a simple theoretical framework that integrates the canonical quantity-quality trade-off into a household bargaining model with limited commitment, where cultural norms are captured by the extent of women's veto power over fertility decisions. Our results highlight the critical role of cultural norms in shaping the effects of policy interventions on fertility behavior and broader development outcomes.
Keywords: J13; I25; N37; 330; fertility; gender norms; free primary education